Engaging pre-service EFL teachers in reflection through video-mediated team micro-teaching and guided discussions. Issue 2 (4th March 2021) - Karakaş, Ali; Yükselir, Ceyhun
ABSTRACT: This study investigates pre-service teachers' engagement in reflection and reflective practice through video-recorded microteaching sessions. Using multiple qualitative tools (i.e. field notes, peer feedback, focus group discussions), we conducted a case study with 34 EFL pre-service teachers performing microteaching as part of a compulsory language teacher education course at a state university in southwestern Turkey, i.e. Burdur province. Analysed through thematic analysis, the data showed that watching their own video-recorded sessions with guided focus group discussions proved itself useful to involve them in reflection on their practices and notice several issues, which they did not perceive beforehand. Furthermore, developing critical insights into their practices, most participants were observed to make changes in their future practices, e.g. classroom language, time management, choice, and conduct of activities. Building on the theoretical research into the use of videos in microteaching for purposes of reflection and reflective practice, this study shows that using video-recorded sessions with follow-up group discussions is useful for helping pre-service teachers to engage in reflection and critical thinking.